Unit Blocks Play Activity; What Do You See From Their Play? (The Study of Mathematical Thinking Development Children 3 – 5 Years Old) - Eriva Syamsiatin (Jurnal Usia Dini, 2017)
Unit block was one of famous children’s play materials. Children develop and practice variety of skills during play activities with blocks. Unit blocks help children to construct mathematical thinking skills and concept. The study was to reveal early mathematic thinking skills development children age 3-5 years old that showed during playing unit blocks. The unit blocks was used in this was Pratt’s Unit Blocks. Pratt’s block has a unique composition of block about 5 1/2" long by 2 3/4" wide by 1 3/8" in height.  In order to reveal this phenomena qualitative research method was implemented. Participant of the study were children of aged 3-5 years olds at East Jakarta.  Children were observed and interviewed during play. In order to strengthen the data play activities were also documented through photographs. The results shows children’s early mathematic thinking skills for children age 3 – 5  years old by playing unit blocks is children showed early mathematic matching skill such as classifying skill, comparing skill and ordering skill. Children has shown different types in each stage of their live. Theoretically early mathematic skill were performed through play unit blocks activities. Stimulation of early mathematic thinking skill will develop properly if children were have adequate play materials and environment. Blocks play activities can support their academic life later. Keywords: unit blocks, thinking, mathematics, play